2014
DOI: 10.1002/jbm.b.33312
|View full text |Cite
|
Sign up to set email alerts
|

Rapid prototyped sutureless anastomosis device from self‐curing silk bio‐ink

Abstract: Sutureless anastomosis devices are designed to reduce surgical time and difficulty, which may lead to quicker and less invasive cardiovascular anastomosis. The implant utilizes a barb-and-seat compression fitting composed of one male and two female components. The implant body is resorbable and capable of eluting heparin. Custom robotic deposition equipment was designed in order to fabricate the implants from a self-curing silk solution. Curing did not require deleterious processing steps but devices demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…However, these devices are only designed to remain in place temporarily. In 2016, Jose and colleagues [ 78 ] published preliminary laboratory results on a prototype anastomotic device made of a silk:glycerol bio-ink solution deposited in 40 µm monolayers. They showed that their device is potentially resorbable in vivo, potentially allowing for long-term placement, and could be secured in under a minute [ 78 ].…”
Section: New Directions and Outlookmentioning
confidence: 99%
“…However, these devices are only designed to remain in place temporarily. In 2016, Jose and colleagues [ 78 ] published preliminary laboratory results on a prototype anastomotic device made of a silk:glycerol bio-ink solution deposited in 40 µm monolayers. They showed that their device is potentially resorbable in vivo, potentially allowing for long-term placement, and could be secured in under a minute [ 78 ].…”
Section: New Directions and Outlookmentioning
confidence: 99%
“…It is a biocompatible material that has good mechanical properties than can be tuned with the manufacturing process. In addition, other materials can be blended with the bioink to add characteristics that enhance the outcome of the solution, such as glycerol to add elasticity [ 71 ]. Additionally, it has shown good hemocompatibility, since it does not cause thrombogenic events and expresses solid cell colonization.…”
Section: Discussionmentioning
confidence: 99%
“…The assembled devices demonstrated a compressive strength comparable to self-expanding metal stents. Plus, it resisted pressure bursts greater than the physiological conditions [ 71 ]. The surgery time was reduced to approximately 1 min due to the new silk-based graft approach.…”
Section: Cardiovascular Tubular Applicationsmentioning
confidence: 99%
“…[32] Therefore, achieving cell printing at high viscosity while maintaining acceptable cell viability during the printing process is one of the major challenges of extrusion bioprinting. [15,33] Extrusion bioprinting is also promising to deposit multicellular spheroids to greatly improve the efficiency of tissue fabrication.…”
Section: Extrusion Bioprintingmentioning
confidence: 99%